26ODe-escalating axillary surgery according to neoadjuvant single or dual HER2 blockade in clinically node-positive, HER2-positive breast cancer. (24th November 2019) - Cha, C; Kim, D; Lee, J; Park, S; Bae, S J; Kim, J Y; Ahn, S G; Park, H S; Park, S; Kim, S I; Cho, Y U; Jeong, J
Abstract: Background: Incorporating HER2-blockade into neoadjuvant drug regimens have led to a higher pathologic response in HER-positive breast cancer. In a view point of surgeon, a higher response to neoadjuvant treatment may offer a chance for de-escalating axillary surgery in patients with node-positive breast cancer at initial presentation. We investigated the rates of axillary lymph node dissection (ALND) and pathologic nodal response according to the types of neoadjuvant treatments including single or dual HER2 blockade in patients with clinically node-positive, HER2-postive breast cancer. Methods: We retrospectively reviewed medical records from two institutions. From 2007 to 2018, patients with clinically node-positive, HER2-positive breast cancer treated with neoadjuvant chemotherapy were included. Primary outcome was the ALND rates after SLNB according to regimens. Secondary outcome was incidence of nodal pathologic complete response after axillary surgery. Results: In a total, 512 patients were included for analysis. Two hundred and eighty-five patients (55.7%) were treated with chemotherapy alone, 135 (26.4%) with chemotherapy and trastuzumab, and 92 (18.0%) with chemotherapy, trastuzumab and pertuzumab. Nodal pCR rates were 45.6%, 77.8%, and 78.4% in each group (p-value < 0.0001). However, there was no difference in nodal pCR rates according to single or dual HER2-blockade (p-value = 0.778). In patients undergoing SLNB first, the ALND rates were 93.4%, 72.4%, and 71.6% in each group (p-value < 0.0001). The ALND rates were not different between two groups with single or dual HER2-blockade (p-value = 0.919). In 132 patients with more than three sentinel lymph nodes retrieved, the incidences of nodal pCR indicating the candidates for omission ALND were 44.3%, 86.2%, and 87.9% in each group (p-value < 0.0001). Conclusions: For patients with node-positive, HER2-positive breast cancer, incorporating trastuzumab into neoadjuvant treatment had led to higher nodal pCR and reduced ALND. However, dual HER2-blockade with pertuzumab did not lead to increase nodal pCR and might not offer a chance of de-escalating axillary surgery compared to single HER2-blockade. Legal entity responsible for the study: The authors. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.